Analysis of notifications of suspicions of diseases caused by the way the job is performed in the context of pathologies regarded as occupational diseases - Elżbieta Cwynar; Maria Kosińska; Martyna Tomczyk-Socha (Nofer Institute of Occupational Medicine, 2013)
Background: In this report the increase in the number of notifications of suspicions of diseases caused by the way the job is performed, observed recently in the Regional Center of Occupational Medicine in Wrocław, is highlighted. The problem stems from the recognition of medical certification of such diseases as occupational diseases only in one third of all notifications of suspicions. Material and Methods: The case study was based on statistical data concerning notifications of suspected occupational diseases collected in the Branches of the Regional Center of Occupational Medicine in Wrocław in the years 2006-2011, as well as on medical certificates issued by the Center's Out-patient Clinics of Occupational Diseases. More than 700 reports of suspected chronic occupational diseases of the musculo-skeletal system and chronic diseases of the peripheral nervous system caused by the way the job is performed were analyzed, taking into account gender, age and how the work had been done. On the basis of the analysis of medical certificates issued by physicians, decision-making procedures and the recognition of occupational disease certification are discussed. Results: The analysis of the data collected in the Regional Center of Occupational Medicine, Wroclaw, in the years 2006-2011 showed a significant increase in the percentage of notifications of suspicions of diseases caused by the way the job is performed. At the same time it was shown that only about one third of reported suspicions were concluded with issuing medical certification of an occupational disease and the administrative confirmation of the decision. Conclusions: The results of the study revealed significant certification problems in the group of diseases caused by the way the job is performed in terms of the recognition of this type of pathology as an occupational disease. These issues are ambiguous because of a large number of non-occupational factors involved in the pathogenesis of these diseases. Med Pr 2013;64(3):387-396